Flies improve the salience of iridescent sexual signals by orienting toward the sun. (14th October 2020) - White, Thomas E; Latty, Tanya
Abstract: Sunlight is the ultimate source of most visual signals. Theory predicts strong selection for its effective use during communication, with functional links between signal designs and display behaviors a likely result. This is particularly true for iridescent structural colors, whose moment-to-moment appearance bears a heightened sensitivity to the position of signalers, receivers, and the sun. Here, we experimentally tested this prediction using Lispe cana, a muscid fly in which males present their structurally colored faces and wings to females during ground-based sexual displays. In field-based assays, we found that males actively bias the orientation of their displays toward the solar azimuth under conditions of full sunlight and do so across the entire day. This bias breaks down, however, when the sun is naturally concealed by heavy cloud or experimentally obscured. Our modeling of the appearance of male signals revealed clear benefits for the salience of male ornaments, with a roughly 4-fold increase in subjective luminance achievable through accurate display orientation. These findings offer fine-scale, causal evidence for the active control of sexual displays to enhance the appearance of iridescent signals. More broadly, they speak to predicted coevolution between dynamic signal designs and presentation behaviors, and support arguments for a richer appreciation of the fluidity of visual communication. Abstract : The appearance of colorful ornaments depends on how they are illuminated. Selection should therefore favor the active use of sunlight in visual communication. We test this prediction using a ground-dwelling fly and show that males orient their iridescent faces and wings toward the sun during elaborate courtship dances. This improves the brilliance of their signals to courted females and may serve to inform about their quality as potential mates.